The strategy of business survival in Mahaka Radio Integra Group Jakarta - Sunandar, Ronal; Hidayat, Dadang Rahmat; Yudhapramesti, Pandan (Faculty of Communication Sciences Universitas Padjadjaran, 2025)
Mahaka Radio Integra (MARI) Group Jakarta is a radio group that utilizes new media to sustain its business through integrated marketing communications. The purposes of this research is to determine the strategy of business survival in MARI Group Jakarta through analyze planning, implementation and evaluation. The research use qualitative approach and case study method. The research found that the MARI group's IMC planning involved identifying the target audience, establishing a consistent message, and selecting the media. The implementation includes advertising, sales promotion, public relations, personal selling, digital/Internet marketing, and direct marketing. MARI Jakarta evaluates IMC elements, and starting when the implementation of IMC elements has carried out, evaluation activities run everyday. The evaluation is conducted by collecting data and information on developing IMC elements to measure the success of messages and campaigns, identify strengths and weaknesses, and provide directions and improvements for subsequent IMC implementation. The group of MARI need to integrate teamwork, to plan advertising elements, including advertising campaigns, to select media, to fund management, and to implement IMC elements through good management.